Perception and knowledge about COVID-19: A characterization through surveys - Iglesias-Osores, Sebastián (2021)
Objetive. To describe the perceptions and knowledge about COVID-19. Material and Method: Cross-sectional study, an online survey of 314 participants was conducted, the questionnaire consists of 9 multiple-choice questions, the data were analyzed using descriptive statistics. Results: The average age of the respondents was 26.9 years, the sample comprised more women 161 (51.3%) than men and almost 89% of the respondents belonged to undergraduate, the place of origin of the Covid-19 was well known 94.30%, for half of the respondents 159 (50.6%) it is not a zoonotic disease, concerning the COVID-19 prevention measures the majority of the respondents consider that handwashing is an of the main prevention measures. Conclusion: CAP studies are important for a better understanding of the perception and knowledge of COVID-19. The study revealed that respondents generally have some general knowledge about SARS-CoV-2.